'Bums off seats': measuring the effects of active learning in an undergraduate molecular biology curriculum. Issue 1 (1st January 2022) - Heinemann, Jack A.; Goldstien, Sharyn
ABSTRACT: Institution-crippling earthquakes limited teaching contact hours and range of teaching environments. New ways became needed to achieve the same learning outcomes in less time. Following that disaster, new methods based on active and test-enhanced learning were introduced into two undergraduate molecular biology courses. The courses had a mixture of lecture, laboratory and tutorial environments supported by digital online resources and assignments. The courses formed a series with one being an essential pre-requisite of the other. The introduced methods were assessed over multiple years for learning effectiveness relative to defined goals. Test-enhanced learning had a significant effect on students in the lower level course but was ineffective for higher level learners. Skills learned through test-enhanced learning, however, did not improve performance on new tasks. Use of active learning environments had no significant effect on the performance of lower level learners in subsequent tasks. The performance of higher level learners, however, exceeded expectations from their measured entry competence. The students' assessment of teaching quality negatively correlated with the proportion of active learning. The findings help inform how to achieve better learning outcomes at different maturity levels. In addition, the results reveal potentially important institutional obstacles to achieving these goals.